The Penguatan Karakter Siswa Melalui Penerapan Profil Pelajar Rahmatan Lil Alamin: Strengthening Student Character Through the Implementation of the Rahmatan Lil Alamin Student Profile - Febrianto, Akbar Dwi (Gerasi Insan Nusantara, 2025)
The purpose of this study was to describe the planning, implementation, and evaluation of teachers in the application of P2RA to improve students' civilized character at Nabatul Ulum Islamic Elementary School, Siman, Kepung, Kediri. This study uses a qualitative research approach with a descriptive qualitative research type. The data collection technique is through observation, interviews, and documentation. Data were analyzed by reducing data, presenting data, and concluding. The results of the study indicate that (1) planning for strengthening civilized character is carried out through work meetings to determine objectives, learning tools that are in accordance with student characteristics and designing relevant activities and cognitive, affective, psychomotor assessments, (2) implementation of character focuses on civilized values. Teachers develop student character through communication, positive activities, and provide feedback and rewards. (3) Evaluation is carried out with tests, quizzes, and individual or group assignments. Teachers observe and reflect on students' experiences in learning. Self-assessment, peer assessment, and parent evaluation have been carried out to measure changes in student character in everyday life. Optimizing learning objectives and strengthening character through end-of-semester meetings.